(untitled) (Світ фінансів, 2017)
Вацлавський О. І. Оцінка ефективності бюджетного контролю в Україні. Досліджено теоретичний підхід визначення змісту ефективності бюджетного контролю. Запропоновано запровадити єдину систему показників для оцінки ефективності бюджетного контролю, яка дасть змогу оцінювати ступінь досягнення поставлених цілей щодо підвищення ефективності використання бюджетних ресурсів держави за допомогою комплексу таких критеріїв: продуктивності, концентрації, структурності, дієвості та динамічності. Окреслено основні недоліки, котрі були виявлені при оцінці ефективності бюджетного контролю. Визначено шляхи покращення бюджетного контролю в Україні. Вацлавский О. И. Оценка эффективности бюджетного контроля в Украине. Исследован теоретический подход определения содержания эффективности бюджетного контроля. Предложено ввести единую систему показателей для оценки эффективности бюджетного контроля, позволяющую оценивать степень достижения поставленных целей по повышению эффективности использования бюджетных ресурсов государства с помощью комплекса следующих критериев: производительности, концентрации, структурности, действенности и динамичности. Определены основные недостатки, которые были выявлены при оценке эффективности бюджетного контроля. Определены пути улучшения бюджетного контроля в Украине. Vatslavskyi O. Evaluating the effectiveness of budgetary control in Ukraine. Introduction. Provision of sustainable development requires efficiency in the management of public financial resources. Every year the number of detected financial irregularities supervisory authorities increases. Reduce the amount of possible financial irregularities by increasing the efficiency of budgetary control. The main purpose of the scientific research is to evaluate the efficiency of budgetary control in Ukraine. Results.The effectiveness of budgetary control is a complex economic category .It is characterized by certain criteria and depends on many parameters and factors. In assessing the effectiveness of budgetary control and the development of practical methods of calculation and formation performance criteria should take into account not only the economic component but also various other components efficiency. Monitoring the effectiveness of budgetary control carried out according to certain criteria by examining different interrelated indicators. In our opinion, the most thoroughly evaluate the effectiveness of budgetary control are the following criteria: performance criteria, the criterion of concentration, structuring criterion, criterion validity, criterion dynamism. Conclusion. The introduction of a single integrated system of indicators to assess the effectiveness of budgetary control will help assess the achievement of goals to improve the efficiency of budget resources of the state through a set of criteria: performance, concentration, structuring, efficiency and agility. Using the general method facilitate assessment of the effectiveness of public spending as between different supervisory authorities and between the different territorial units of those bodies.